Asymmetric dimethylarginine and related metabolites in exhaled breath condensate of children with cystic fibrosis. (20th June 2016) - Lucca, Francesca; Da Dalt, Liviana; Ros, Mirco; Gucciardi, Antonina; Pirillo, Paola; Naturale, Mauro; Perilongo, Giorgio; Giordano, Giuseppe; Baraldi, Eugenio
Abstract: Introduction: Asymmetric dimethylarginine (ADMA) competitively inhibits nitric oxide synthase (NOS). Its levels in specimens from murine models and asthmatic patients are related to inflammation and oxidative stress. Patients with cystic fibrosis(CF) reportedly have higher arginase activity, lower NO production and NOS expression than healthy controls. Objective: The objective was to assess the role of ADMA and related metabolites as disease biomarkers in exhaled breath condensate (EBC) of pediatric CF patients, compared with age‐matched healthy controls (HC). Methods: A longitudinal design was conceived and 34 CF patients (21 stable, 13 at the onset of exacerbation) and 16 HC were enrolled. All CF patients underwent clinical examination, spirometry and EBC collection at enrolment; the same tests were performed also after an antibiotic course in those patients with exacerbation. Metabolites levels in EBC were measured with an ultra‐performance liquid chromatography and tandem mass spectrometry technique. Results: All CF patients had ADMA levels (expressed as ratio to tyrosine) similar to those in HC (median 0.0112, IQR 0.0103‐0.0120 and median 0.0114, IQR 0.0090–0.0128, respectively; P  = 0.983), while a significant increase in the citrulline/tyrosine ratio was found in CF patients (median 0.6419, IQR 0.5738–0.6899 in CF vs median 0.4176, IQR 0.2986–0.5082 in HC; P  = 0.00003). No differences in ADMA levels emerged between stable patients and those with exacerbation. Conclusion: ADMA and related aminoacids were measured simultaneously for the first time in EBC from CF patients. Higher citrulline/tyrosine ratios were found in CF children with normal ADMA levels, suggesting a dysregulated ADMA metabolism in these patients.